Collisional and radiative pumping in 22-GHz water masers. Issue 1 (29th March 2022) - Gray, M D; Etoka, S; Richards, A M S; Pimpanuwat, B
ABSTRACT: We briefly discuss the history of pumping schemes for the common 22-GHz maser transition in o-H2 O, and note that radiative mechanisms have been considered in the past, as well as the better known collisional pumping mechanisms associated with shock waves. Substantial IR irradiation is indeed destructive to inversion at 22-GHz under a wide range of physical conditions. We identify a small number of transitions, including 22 GHz, that can be pumped by both collisional and radiative schemes, and, through radiative transfer modelling over a grid of values in kinetic temperature, number density, and dust temperature, identify loci in density-kinetic temperature space where these schemes lead to strong inversions. The radiative pumping scheme generally operates at higher dust temperature, and lower kinetic temperature, than the collisional scheme. We identify a small network of transitions that form a radiative pumping scheme for the 22-GHz maser, involving radiative transitions of wavelength approximately 6 $μ$ m. This network is capable of supplying more than 50 per cent of the 22-GHz inversion under typical radiative pumping conditions, and it is consistent with the need for high dust and low kinetic temperatures determined from the modelling. We identify a probable case of radiative pumping in a massive star-forming region from the observation of a positive correlation between the flux densities of 22-GHz H2 O masers and 6.7-GHz methanol masers. We discuss possibilities for finding radiatively pumped H2 O maser lines in other source types.